Efficacy and Safety of Transcanal Endoscopic Ear Surgery for Congenital Cholesteatomas: A Preliminary Report. Issue 10 (December 2015) - Kobayashi, Taisuke; Gyo, Kiyofumi; Komori, Masahiro; Hyodo, Masamitsu
Abstract: Objective: Transcanal endoscopic ear surgery (TEES) can provide greater visual access during resection of middle ear disease than the operating microscope. The purpose of this study was to determine the safety and efficacy of TEES when used for the management of congenital cholesteatoma (CC) in children. Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: Twelve children with CC confined to the middle ear underwent TEES. Seven children were Potsic stage I, four were stage II, and one was stage III. The mean follow-up period was 23.1 months. Intervention: Transcanal middle ear surgery using endoscopes. Main Outcome Measures: Incidence of surgical complications and cholesteatoma recurrence. Results: Twelve patients underwent TEES and four patients underwent microscopic surgery during the same period. No surgical complications occurred. Postoperative audiograms were available for 7 of 12 patients who had puretone averages ranging from 3.3 to 23.9 dB HL (mean, 12.7 dB HL). One patient with a stage III CC was found to have residual disease during a second-look procedure, whose follow-up period was only 3 months. Other patients underwent one-stage operations and have developed no cholesteatoma recurrence. Conclusion: Although the follow-up period and number of patients were limited, early-stage CC can be safely removed using TEES.